Evaluating urban shape of Tehran through differential semantics scale. Issue 1 (1st January 2021) - Latifi, Gholamreza; Paknezhad, Navid
Abstract: The urban landscape and the image of the city by which the observers judge about a city remain as the mental image of a city in the mind of a man The urban landscape is capable of depicting the historical events of urban society. The favorable urban landscape has always been different from different people's perspectives and the use of different approaches to summarize the perspectives of people in a practical and correct way has always been a concern of researchers in this field. This study attempted to explain the ideas and perspectives of the target population (including university professors, experts, consulting engineers, and urban managers) using the differential semantics technique. In so doing, a qualitative research design was used to explore the features of an appropriate urban landscape for the city of Tehran through differential semantics. The questionnaire was designed based on three main dimensions: evaluative, power, and activity, which were measured on a seven-point differential semantics scale. The participants were asked to select the images which are closest to the urban landscape of Tehran. Results showed that two pictures were selected as the ideal landscape of Tehran in the future.